Civil liability derived from occupational accidents - Ayvar Roldán, Carolina (2019)
Civil liability resulting from work related accidents stems from the employer-employee relationship, since the employer undertakes to protect the life, health and welfare of his employees at the workplace and must assume the legal or economic implications produced by them, responding for the damages caused, regardless of whether such damages imply loss of profit, ensuing damages, moral damages and even personal harm, since the existing case law has established their scope. However, given the reality in the occupational realm, especially in relation to risky work obligations, it largely exceeds the doctrinal or jurisprudential provisions, particularly in terms of determining the amount of compensation and the establishment in each case, of the liability of the employer and the reparation of the damages.